Human Immunodeficiency Virus Persistence and T-Cell Activation in Blood, Rectal, and Lymph Node Tissue in Human Immunodeficiency Virus–Infected Individuals Receiving Suppressive Antiretroviral Therapy. (7th February 2017) - Khoury, Gabriela; Fromentin, Rémi; Solomon, Ajantha; Hartogensis, Wendy; Killian, Marisela; Hoh, Rebecca; Somsouk, Ma; Hunt, Peter W.; Girling, Valerie; Sinclair, Elizabeth; Bacchetti, Peter; Anderson, Jenny L.; et al.
Abstract: Background: Immune activation and inflammation remain elevated in human immunodeficiency virus (HIV)–infected individuals receiving antiretroviral therapy (ART) and may contribute to HIV persistence. Methods: Using flow cytometry expression of CD38, HLA-DR and PD-1 were measured in blood (n = 48), lymph node (LN; n = 9), and rectal tissue (n = 17) from virally suppressed individuals. Total and integrated HIV DNA, 2-LTR circles, and cell-associated unspliced HIV RNA were quantified. Results: CD4 + T cells from rectal tissue had a higher frequency of integrated HIV DNA compared with blood (4.26 fold-change in DNA; 95% confidence interval [CI] = 2.61–7.00; P < .001) and LN (2.32 fold-change in DNA; 95% CI = 1.22–4.41; P = .01). In rectal tissue, there were positive associations between integrated HIV DNA with PD-1 + CD4 + T-cells (1.44 fold-change in integrated HIV DNA per 10-unit increase in PD-1 + CD4 + T cells; 95% CI = 1.01–2.05; P = .045) and CD38 + HLA-DR + CD8 + T cells (1.40 fold-change in integrated HIV DNA per 1-unit increase in CD38 + HLA-DR + CD8 + T cells; 95% CI = 1.05–1.86; P = .02). Both associations were independent of current and nadir CD4 + T-cell counts. Conclusions: During ART, rectal tissue is an important reservoir for HIV persistence with a high frequency of activated CD4 + and CD8 + T cells. PD-1 may represent a marker of HIV persistence in rectal tissue.